Implication of Omnibus Law's Assessment on the Perspective of Employment Regulation - M. Syahrul Borman; Dudik Djaja Sidarta; Nur Handayati (Global Writing Academica Researching & Publishing, 2023)
The Work Copyright Bill and the Tax Bill are two salient components of the Omnibus Law Bill, which warrant careful consideration. Both of these bills hold significant importance in their respective contexts. According to Joko Widodo, the President of the Republic of Indonesia, the primary objective behind the introduction of the Omnibus Law Bill is to alleviate the burdensome regulatory constraints that often lead to confusion and protracted processes. The rationale behind the enactment of the Omnibus Law Bill was articulated as such. It is expected that the forthcoming comprehensive legislation will contribute to the enhancement of the national economy by creating a more favourable investment climate. Additionally, the objective of this initiative is to enhance Indonesia's competitiveness, enabling it to effectively navigate the prevailing economic uncertainty and deceleration observed worldwide. The data collection in this study employed an empirical research approach. The execution of this technique involved the careful examination of multiple facets of research specialism, including the utilisation of descriptive analysis. This paper provides a synthesis of scholarly discussions on the legal implications of the ratification of the omnibus law bill on job creation for the relationship between companies and their employees. Specifically, it examines the impact of this legislation on the legal framework and practises of civil and employment law. The purpose of these research was to establish a definitive legal standpoint about the consequences of ratifying the omnibus law bill on employment creation.